2019
DOI: 10.1021/acs.jctc.8b01211
|View full text |Cite
|
Sign up to set email alerts
|

Intricacies of DFT+U, Not Only in a Numeric Atom Centered Orbital Framework

Abstract: We implemented the popular Hubbard density-functional theory + U (DFT+U) method in its spherically averaged form in the all-electron, fullpotential DFT code FHI-aims. There, electronic states are expressed on a basis of highly localized numeric atomic orbitals (NAO), which straightforwardly lend themselves as projector functions for the DFT+U correction, yielding the necessary occupations of the correlated Hubbard subspace at no additional cost. We establish the efficacy of our implementation on the prototypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 74 publications
(139 reference statements)
3
63
0
Order By: Relevance
“…We note that all DFT+U results presented here are based on the implementation of the Dudarev formalism in VASP. Different DFT+U implementations may yield different results 30 .…”
Section: Resultsmentioning
confidence: 99%
“…We note that all DFT+U results presented here are based on the implementation of the Dudarev formalism in VASP. Different DFT+U implementations may yield different results 30 .…”
Section: Resultsmentioning
confidence: 99%
“…21,22 In addition, it depends heavily on the implementation in the DFT code. 42 Thus, we cannot directly compare the absolute values of U , which are taken from different DFT codes. Nevertheless, it can be used as a reasonable model for qualitatively comparing results with those from available theoretical or experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the most recent contribution we computed the MUO 4 compounds with M = Ni, Fe, Co, Cd, and found that only by using the correct projectors for estimation of occupation of d orbitals, e.g., Wannier functions, we could reproduce experimentally seen structural distortions (Murphy et al, 2021). The problem arises from the fact that with the standard DFT+U approach, when using atomic orbitals as projectors, the total occupancy of the d or f states of interest is much higher than the actual one (Kick et al, 2019;Murphy et al, 2021). As illustrated in Table 3, in our case it gives ∼1.3 excess electrons for Fe(III) and ∼0.5 for Fe(II).…”
Section: Structural Datamentioning
confidence: 99%
“…In a series of papers we have shown that standard DFT approach often fails for such cases and these compounds must be carefully computed, including proper accounting for the correlation effects (Beridze and Kowalski, 2014;Blanca-Romero et al, 2014;Kowalski et al, 2015;Li and Kowalski, 2018). These simulations must be performed with methods beyond the standard DFT+U approach and include derivation of the Hubbard U parameter and careful choice of projectors for estimation of occupancy of d− and f − levels within the DFT+U scheme (Maxisch and Ceder, 2006;Kvashnina et al, 2018;Kick et al, 2019). In particular, we apply the linear response method (Cococcioni and de Gironcoli, 2005) with Wannier orbitals as representation of d or f states (Kvashnina et al, 2018) and here we will demonstrate impact of these procedures on the estimation of formation enthalpies and solubility limits of Li x FePO 4 compound.…”
Section: Introductionmentioning
confidence: 99%